Surgical Management of Intracranial Neuroenteric Cysts: The UCSF Experience - Breshears, Jonathan D.; Rutkowski, Martin J.; McDermott, Michael W.; Cha, Soonmee; Tihan, Tarik; Theodosopoulos, Philip V. (Journal of Neurological Surgery Part B: Skull Base, 2015)
Objective Modern surgical experience with intracranial neuroenteric cysts is limited in the literature. We review our 15-year institutional experience with these rare lesions.Design Single-institution retrospective study.Setting Large North American tertiary care center.Participants Histologically confirmed cases of intracranial neuroenteric cyst from January 2000 to September 2014.Main Outcome Measures Pre- and postoperative modified Rankin Scale (mRS) scores, extent of resection, and postoperative complications are reported. Clinical presentation, imaging features, pathology, and operative approach are discussed.Results Five spinal and six intracranial neuroenteric cysts were surgically treated over a 15-year period. Median age at presentation for the intracranial cysts was 38.5 years. Mean cyst diameter was 3.8 cm. Five cysts were located in the pre-pontomedullary cistern, and one was located in the third ventricle. Gross total resection was achieved in four of the five posterior fossa cysts through a far lateral transcondylar approach. Postoperative complications included aseptic meningitis (one), transient abducens palsy (one), and pseudomeningocele requiring reoperation (three). Postoperative mRS scores improved to ≤1 by 6.5 months median follow-up.Conclusions Intracranial neuroenteric cysts are rare lesions with a variable imaging appearance. Complete surgical resection through a far lateral transcondylar approach is possible and usually results in symptom improvement or resolution.
Keywords: neuroenteric cyst; neurenteric cyst; enterogenous cyst; bronchogenic cyst